Continuous-Valued Binary Decision Procedures - Ferejohn, John A.; Grether, David M.; Matthews, Steven A.; Packel, Edward W. (Review of Economic Studies, 1980)
John A. Ferejohn, David M. Grether, Steven A. Matthews, Edward W. Packel; Continuous-Valued Binary Decision Procedures, The Review of Economic Studies, Vol